How Perceived Threats of Air Pollution Affect the Resident’s Purchasing Behavior of Functional Foods - Wu, Ching-Hsiang; Hsieh, Po-Chuen; Pan, Frank (Journal of Asian Business Strategy, 2018)
Air pollution jeopardized human’s health, in particular the respiratory diseases. Along with the industrial development, air pollution had extended effects to the surrounding areas. Plenty of evidence had shown that some functional foods were developed to strengthen the lung health. Based on the health belief model (HBM), this research explored the effects of each contributor on purchasing functional foods. There are 90 valid responses gather from the highly air polluted area, Hsio-Kang district of Kaohsiung. Statistical results indicated that the HBM significantly explained the functional food purchasing behavior for the designated area (R2=22.6). The perceived susceptibility is the strongest predictor (β= 0.42) for the behavior, followed by perceived benefits (β= 0.19), and perceived barriers (β= -0.10). Some implications and suggestions based on the discussion and conclusion were offered for reference.